THE ROLE OF ISLAMIC BUSINESS ETHICS IN INCREASING CUSTOMER LOYALTY ON DIGITAL PLATFORM: A STUDY OF TIKTOK SHOP - Risna Nur Ainia; Siti Rifqiyatul Muttafiyah; Churin In (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
The development of social media-based e-commerce platforms, such as TikTok Shop, encourages business actors to focus not only on marketing strategies but also on the implementation of business ethics, particularly Islamic business ethics. This study aims to analyze the influence of Islamic business ethics values, including honesty, fairness, responsibility, transparency, and adherence to sharia principles, on consumer loyalty on the TikTok Shop platform. This study used a quantitative approach with a survey method. Primary data were obtained by distributing questionnaires to 61 respondents, students of the Faculty of Economics and Business, Universitas PGRI Wiranegara who actively shop on TikTok Shop. Data analysis was conducted using the Partial Least Square (PLS) method with the assistance of SmartPLS software version 4.0. The results showed that honesty, responsibility, and transparency had a positive and significant effect on consumer loyalty. Meanwhile, fairness and adherence to sharia principles had a positive but insignificant effect on consumer loyalty. These findings indicate that not all dimensions of Islamic business ethics have the same level of influence, but in general, the implementation of Islamic business ethics remains important in building and increasing consumer loyalty on digital platforms.